2000
DOI: 10.1203/00006450-200001000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Bone Mineral Content at Term in Premature Infants

Abstract: Premature infants are at risk of developing metabolic bone disease mainly because of low calcium and phosphorus intake. We have examined the effect of different mineral supplements on bone mineral content at term in 127 premature infants with gestational age <32 wk in a double-blinded randomized trial. We used either phosphate supplementation of human milk as recommended by the European Society of Pediatric Gastroenterology and Nutrition or fortified supplementation with protein, calcium, and phosphorus or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 28 publications
2
33
1
6
Order By: Relevance
“…Excessive phosphorus from carbonated beverages may increase the risk of adolescent fractures (Wyshak & Frisch, 1994) as well as impair bone homeostasis (Calvo, 1994). However, phosphorus supplementation leads to short-term increases in growth in preterm neonates (Faerk et al, 2000) while phosphorus intake is positively associated with BMD in young women (Teegarden et al, 1998) and postmenopausal women (Tranquilli et al, 1994). There have been few reports relating fat intake to BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive phosphorus from carbonated beverages may increase the risk of adolescent fractures (Wyshak & Frisch, 1994) as well as impair bone homeostasis (Calvo, 1994). However, phosphorus supplementation leads to short-term increases in growth in preterm neonates (Faerk et al, 2000) while phosphorus intake is positively associated with BMD in young women (Teegarden et al, 1998) and postmenopausal women (Tranquilli et al, 1994). There have been few reports relating fat intake to BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à mineralização óssea, os resultados são conflitantes, com duas pesquisas referindo somente aumento do CMO do rádio 15 e aumento no CMO total 16 , e dois autores citados 17,18 não mostrando diferenças no CMO total com a suplementação. Não foram observadas fraturas, hipercalcemia ou outras manifestações clínicas.…”
Section: Conteúdo De Cálcio Do Leite Humano E De Fórmulasunclassified
“…Second, even though protein enrichment affords short-term growth improvement, no long-term benefits have been demonstrated [8][9][10]. One Danish study suggested that unfortified human milk in daily amounts of around 200 ml/kg might be sufficient for preterm infants; in that study, infants given only their own mothers' unfortified milk were heavier at discharge but had length and head circumference measurements similar to infants fed with preterm formula [11]. Finally, in developing countries exclusively breastfed premature infants with VLBW have shown weight gain comparable to intra-uterine growth rates [12].…”
Section: Introductionmentioning
confidence: 99%